IMMU-42. CD8+ T-CELLS MEDIATE IMMUNOEDITING, AND INFLUENCE GENOTYPE, TUMOR ONCOGENIC PATHWAYS AND MICROENVIRONMENT DURING PROGRESSION OF MURINE GLIOMAS. (11th November 2019) - Robert Kane, J; Zhao, Junfei; Tsujiuchi, Takashi; Laffleur, Brice; Mahajan, Aayushi; Rao, Ganesh; Mela, Angeliki; Dmello, Crismita; Arrieta, Victor A; Chen, Li; Zhang, Daniel Y; Lee-Chang, Catalina; et al.
Abstract: Cancer immunoediting shapes tumor progression by the immunological selection of tumor cell variants that can evade immune recognition. Given the immune evasive cellular diversity of glioblastoma, we hypothesized that CD8+ T-cells mediate immunoediting in this tumor. We evaluated tumor progression in the absence of CD8+ T-cells by depleting this immune cell population in a transgenic murine glioma model. Tumors generated in the absence of CD8+ T-cells developed poorly in recipients with intact immunity, implying a more immunogenic profile. These tumors demonstrated increased chromosomal instability, gene fusions, MAPK signaling, and macrophage infiltration. These observations were stochastic, suggesting variability in the mode of tumor evolution in the absence of this immune effector. MAPK activation was correlated with macrophage recruitment in two transgenic murine models and the human disease. Our results indicate that CD8+ T-cells mediate a strong immunoediting selection in glioblastoma that protect against the hallmarks of cancer and drive immune evasion.